Patient-centred infertility care among Arab women experiencing infertility: a qualitative study. Issue 6 (18th June 2021) - Webair, Hana Hasan; Ismail, Tengku Alina Tengku; Ismail, Shaiful Bahari; Khaffaji, Azza Jameel
Abstract : Objective: The current study aims to define patient-centred infertility care (PCIC) from the perspective of Arab women with infertility. Design: Semistructured in-depth telephone interviews. Setting: Hospitals providing infertility care, Jeddah, Saudi Arabia. Participants: Arab women who received infertility treatment during the 6 months preceding the interview at any hospital in Jeddah, Saudi Arabia. Interviews were conducted with Arab women experiencing infertility from January 2017 to December 2018. A purposive sample of 14 women were included in the final analysis with maximum variation. Results: Participants highlighted nine important PCIC dimensions. Of these, four were agreed on by all participants: accessibility, minimising cost, information and education, and staff attitudes and communication. The remaining five dimensions were staff competence, physical comfort, privacy, psychological and emotional support, and continuity and coordination of care. The concept of PCIC was related to three major contributors: participants' demographics, patient experience with infertility care and health-seeking behaviour. Conclusions: The current study provided nine PCIC dimensions and items, which can guide efforts to improve the quality of infertility care in Arab countries in two ways: first, by raising infertility care providers' awareness of their patients' needs, and second, by developing a validated tool based on the dimensions for measuring PCIC from Arab patients' perspective. Clear differences between the Arab and the European PCIC model were found. Our findings concluded that women continued to exhibit basic unmet needs.